OSgc: A Web Portal to Assess the Performance of Prognostic Biomarkers in Gastric Cancer - Xie, Longxiang; Wang, Qiang; Yan, Zhongyi; Han, Yali; Ma, Xiaoyu; Li, Huimin; Zhang, Lu; Li, Xianzhe; Guo, Xiangqian (Frontiers in Oncology, 2022)
Evaluating the prognostic value of genes of interests in different populations of Gastric cancer (GC) is difficult and time-consuming for basic and translational researchers even though many datasets are available in public dataset depositories. In current study, we developed a robust web-based portal called OSgc (Online consensus Survival analysis of gastric cancer) that enable easy and swift verification of known and novel biomarker candidates in GC. OSgc is comprised of gene expression profiling data and clinical follow-up information of 1824 clinical GC cases, which are collected from 7 public independent datasets derived from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA). By OSgc, users input the official gene symbol and will promptly retrieve the Kaplan Meier survival plot with hazard ratio (HR) and log rank p value on output webpage, by which users could assess the prognostic value of interesting genes for GC patients. Five survival end points containing overall survival, progression free survival, progression free interval, relapse free survival and disease free survival could be measured in OSgc. OSgc can greatly help cancer biologists and clinicians to explore the effect of gene expression on patient survival. OSgc is freely available without restrictions at http://bioinfo.henu.edu.cn/GC/GCList.jsp.